Sarcocystis moreliae sp. nov. in the imported green tree python Morelia cf. viridis (Reptilia, Pythonidae) - Máca, Ondřej; González-Solís, David (Frontiers in Veterinary Science, 2023)
Species of Sarcocystis use various vertebrates as intermediate or definitive hosts in their life cycles. One of them are snakes, whose role as intermediate hosts for these protozoans is scarce; in fact, there are six records, but only three with a molecular characterization. An imported green tree python allowed the morphological and molecular characterization (four loci) of a new species of Sarcocystis localized in skeletal muscles. Sarcocystis moreliae sp. nov. has a type 1 sarcocyst with smooth wall and it is genetically similar (at 18S rRNA) to two unnamed species of Sarcocystis found in Lytorhynchus diadema from Oman and Varanus salvator macromaculatus from Malaysia, but their comparison is impossible. The new species showed lower similarity to its congeners in the other loci (28S rRNA, ITS1, cox1). This is the first morphological and genetic characterization of a Sarcocystis species in snakes of the genus Morelia and M. viridis by using 4 loci. Absolutely, more data are needed to fulfil the gap of knowledge about snakes as intermediate hosts of Sarcocystis.